Pendekatan Kritis Implementasi Akad Wadi’ah pada Perbankan Syariah Indonesia - Muslih Candrakusuma (Falah: Jurnal Ekonomi Syariah, 2016)
As a natural situation, the Islamic banking industry not only have a chance, but also the various problems such as problem on products giro and saving syariah based on wadi’ah. In wadi’ah saving, bank syariah receive trustful saving from the client and distributing it to use it optimally. Actually, the use of trustful saving (wadi’ah) is forbidden, but what is applied in the banking industry is wadi’ah used to any project of business. From this point of view, this kind of application more relevant to qard contract than wadi’ah. The purpose of Islamic law  (maqasid al-shari’ah) is to ensure the wealth (hifz al-mal) embodied in the product save deposit box. In save deposit box, wealth entrusted in bank, stored in a special place, that are guarded by the bank. At the level of primary (al-daruriyah), safeguarding the wealth is a basic need for Muslim. So that, the sustainability of safeguarding of wealth should be championed.